PERENCANAAN SISTEM INFORMASI WEB PEMESANAN LAYANAN FOTOGRAFI PADA CABELL SHOT - Sandy Duta Alam; Agus Budiyantara; Irvan Lewenusa (Fakultas Teknologi Informasi Universitas Tarumanagara, 2025)
This study aims to build a web-based information system that can simplify the process of ordering photography services at Cabell Shot, which is one example of progress in the field of technology by utilizing information technology. This system is built with the Scrum development method and uses the PHP programming language with the Laravel 11 framework. The plan for the results of this study is that the system developed will be able to improve the efficiency and accuracy of the customer ordering process, provide satisfaction for customers and also facilitate the Cabell Shot team in processing order data, services, and photographers. The planning of this system is expected to be a reference for the development of similar systems in other photography businesses and increase Cabell Shot's competitiveness in the photography industry.